A smartphone-based wearable sensors for monitoring real-time physiological data. (January 2018) - Leu, Fang−Yie; Ko, Chia−Yin; You, Ilsun; Choo, Kim-Kwang Raymond; Ho, Chi-Lun
Highlights: The proposed system provides real-time feedback, i.e., issuing alert messages, when one or some of the vital signs, including temperature, ECG, HR, BP, BG, and SpO2, of a monitored patient are abnormal. This can shorten the time period from the occurrence of the abnormal to the time when caregivers reach the patient so that they can assist the patient as soon as possible. The physiological data collected in the MoPSS can be the big data, from which indicators of possible diseases may be discovered. This is one of the steps of preventive medicine. We propose an innovative approach to synchronize the data collection from sensors, which are produced by different manufacturing companies, with different versions of Bluetooth protocols. The personal health information gathered in the healthcare cloud enables medical professions and caregivers to access it for monitoring anytime and anywhere without restricting themselves in a specific geographical area. Abstract: Recently, Wireless Body Sensor Networks (WBSNs) have been popularly employed to measure people's physiological parameters, particularly for disease monitoring, prevention, and treatment. In this study, we propose a smartphone-based WBSN, namedMo bileP hysiologicalS ensorS ystem (MoPSS), which collects users' physiological data with body sensors embedded in a smart shirt. A patient's vital signs are continuously gathered and sent to a smart phone in a real-time manner. The data are then delivered to a remote healthcare cloud via WiFi. After performing necessary classification and analysis, the health information of individual patients is also stored in the cloud, from which authorized medical staffs can retrieve required data to monitor patients' health conditions so that when necessary, caregivers are able to reach the patients as soon as possible and provide required assistance. Our simulations demonstrate that the presented healthcare system provides a better solution for health management. Graphical abstract: The MoPSS platform contains wireless body sensor network system, wireless router, data collection and classification system (comprising data collection server and data classification server) and healthcare monitor system (comprising healthcare cloud and monitor websites).